EVALUASI KEBERLANJUTAN PENGELOLAAN SAMPAH KOTA PADANG: PENDEKATAN BERBASIS KEBIJAKAN PUBLIK MELALUI ANALISIS MDS-RAPFISH - Meuraksa, Irawati; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to evaluate the sustainability of waste management in Padang City through a public policy-oriented approach using the Multi-Dimensional Scaling (MDS) method with a modified RAPFISH (Rapid Appraisal for Fisheries) framework. The evaluation covers five key dimensions of sustainability: economic, environmental, social, technological and infrastructure, and institutional. Primary data were collected through interviews with key informants, while secondary data were obtained from policy documents and relevant literature. The results indicate that all five dimensions fall into the "less sustainable" category, with an average sustainability index score of 35.78. The technology and infrastructure dimension recorded the lowest score (18.53), highlighting the urgent need for policy interventions in this area. Leverage and Monte Carlo analyses identified the most sensitive attributes affecting sustainability, namely waste transportation infrastructure and the safety and comfort of waste management facilities. These findings provide a critical foundation for the formulation of systemic, integrative, and evidence-based public policies to enhance the effectiveness and sustainability of waste management in Padang City.